Pedagogical conditions of development and self-development of students in the process of professional training in higher education (Pedagogy of Higher and Secondary Education, 2021)
In the article the pedagogical conditions of forminf the abilities to development and self-development of students during their proffesional training are considered.
Keywords: abilities of students to development and self-development; personal, act and dialogical approach in the process of study